The First Wave of COVID-19 Pandemic: Sociodemographic Characteristics of Patients in A Tertiary Level Hospital of Bangladesh - Das, Shuva; Hoque, Md Ehsanul; Rudra, Sujan; Kalam, Abul; Rahman, Mohammad Arifur; Paul, Sujat; Sharmin, Sabrina; Das, Priyatosh; Sultana, Afreen; Rosy, Mosammat Jahanara (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: The COVID-19 has led to more than 120 million confirmed cases, with over 2.6 million deaths globally, as of March 2021. As the outbreak continues, several research activities regarding the first wave have been conducted to better understand the incidence and prevention methods. This record will play an important role to take more precautions for overcoming the second wave. Materials and methods: In this retrospective cohort study, we collected the age, sex, and the locality of the suspected and SARS-CoV-2 positive patients and tried to make a bridge among them. We conducted rRT-PCR in the Molecular Biology Laboratory of Chittagong Medical College, Chattogram in between May and August 2020. After that, we used a decision tree and time series evaluation to analyze the data. Results: The highest (50.35%) positive cases were detected in the 3rd and 4th week of May. Men were significantly infected (66.2%) more than women. The 31-40 year age group was mainly affected (24.4%), and 88% of the cases belonged to urban areas. Conclusions: The distribution of cases varied with time, and it will guide the physicians to give better support to humanity. JCMCTA 2021 ; 32 (1) : 65-71